Komponen Pembelajaran dalam Perspektif Pendidikan Islam - Fahrudin (IIQ An Nur Yogyakarta, 2022)
This study aimed to describe in depth for a complete understanding of the importance of learning components in the perspective of Islamic education, using a library study approach that focuses on literature review as the main source in exploring the themes raised. The results of this study indicated that the learning components such as students, learning materials, teachers, learning objectives, learning methods, learning media and learning assessment in the perspective of Islamic education were closely related. Therefore, as the main actor, the teacher should optimize his professional efforts in supervising, guarding, motivating, and guiding his students during the learning process. So that the existing learning components could be run properly and optimally.